VIBRATING-UPLIFT ROCKING MOTION OF CAISSON BREAKWATERS UNDER VARIOUS BREAKING WAVE IMPACT FORCES - 王元战 周枝荣 杨海东 (Applied mathematics and mechanics, 2005)
Overturning is one of principal failure types of caisson breakwaters and is an essential content of stability examination in caisson breakwater design. The mass-springdashpot model of caisson-foundation system is used to simulate the vibrating-uplift rocking motion of caisson under various types of breaking wave impact forces, i. e., single peak impact force, double peak impact force, and shock-damping oscillation impact force. The effects of various breaking wave types and the uplift rocking motion on dynamic response behaviors of caisson breakwaters are investigated. It is shown that the dynamic responses of a caisson are significantly different under different types of breaking wave impact forces even when the amplitudes of impact forces are equal. Though the rotation of a caisson is larger due to the uplift rocking motion, the displacement, the sliding force and the overturning moment of the caisson are significantly reduced. It provides the theoretical base for the design idea that the uplift rocking motion of caisson is allowed in design.